Protective effects of topical alpha-tocopherol acetate on UVB irradiation in guinea pigs: Importance of free radicals - Saral, Y; Uyar, B; Ayar, A; Naziroglu, A (Acad Sciences Czech Republic, Inst Physiology, 2002)
Reactive oxygen species can be generated by daily exposure of the skin to ultraviolet light and may cause some subchronic and chronic skin disorders. The aim of this study was to investigate a possible preventive role of alpha-tocopherol acetate (ATA) on ultraviolet B (UVB) induced peroxidation by assessing lipid peroxide (LPO) levels and activity of reactive oxygen scavenging enzymes including glutathione peroxidase and superoxide dismutase (SOD) in guinea pigs. ATA was topically applied to the skin for three weeks before a single dose of 0.9 J/cm(2) UVB irradiation on the skin and lipid peroxide levels and antioxidants in plasma, skin and liver and erythrocytes were determined after decapitation. Topical application of ATA prevented the UVB irradiation-induced reduction of scavenging enzyme activities in skin and erythrocytes. In conclusion, we suggest that topical applications of ATA before UVB irradiation is effective in protecting the skin from unwanted effects of UVB irradiation.
Keywords: alpha-tocopherol; antioxidants; guinea pig; lipid peroxide; skin; ultraviolet B